Personality and family social climate in adolescents of nuclear biparent and single-parent family - Chuquimajo Huamantumba, Silvia (2017)
This research raises analyze the differences in the personality and the family social climate of adolescents between who belong to nuclear parent Family and single-parent family. The sample consisted of 254 adolescents between 13 and 19 years of State educational institutions of Metropolitan Lima. We administered the Inventory of adolescents’ personality (MAPI) and the scale of family social climate (FES) adapted by Ruiz and Guerra. The design is descriptive comparative. The results show that the type of family (nuclear parent family and single- parent family) does not influences in the styles of personality, but is influences by the sex. The social family climate and type of family does not show differences significant in the scale, neither in the dimensions. In conclusion, the type of family influence in the personality but not in the social family climate; the type of family that the adolescent belong is not the only relevant variable to affect in the social family climate.